2014
DOI: 10.1038/ncomms5678
|View full text |Cite
|
Sign up to set email alerts
|

Temporal spying and concealing process in fibre-optic data transmission systems through polarization bypass

Abstract: Recent research has been focused on the ability to manipulate a light beam in such a way to hide, namely to cloak, an event over a finite time or localization in space. The main idea is to create a hole or a gap in the spatial or time domain so as to allow for an object or data to be kept hidden for a while and then to be restored. By enlarging the field of applications of this concept to telecommunications, researchers have recently reported the possibility to hide transmitted data in an optical fibre. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…The basic principle of this device was initially proposed in ref. [12]. It is based on the nonlinear cross-polarization interaction in a standard optical fiber between a forward signal and its high-power counter-propagating replica, generated and amplified by a factor g at fiber end by means of a reflective loop setup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic principle of this device was initially proposed in ref. [12]. It is based on the nonlinear cross-polarization interaction in a standard optical fiber between a forward signal and its high-power counter-propagating replica, generated and amplified by a factor g at fiber end by means of a reflective loop setup.…”
Section: Discussionmentioning
confidence: 99%
“…We thus confirm the existence of an attraction regime that, as already observed in ref. [12], is characterized by an upper threshold g A here estimated by the relation g A =9π / (16•L•Ps(L)•). In this regime if a CW SOP s(0,t)=s(0) is injected in the fiber then the corresponding output SOP s(L,t) always converges in time towards a fixed point belonging to the LSOS, which is analogous to the attraction process experienced by S 1 (L,t) in Fig.2(a-c).…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…To this aim, several techniques have emerged in the literature in order to develop a nonlinear polarizer capable to repolarize an incident signal with 100% of efficiency, whilst preserving the quality of the temporal intensity profile. This phenomenon of polarization attraction in optical fibers or polarization pulling effect, has been the subject of numerous studies in the literature involving the Raman effect [35][36][37][38][39][40][41][42][43], the stimulated Brillouin backscattering [44][45][46][47][48][49], the parametric amplification [50][51][52] as well as a counter-propagating four-wave mixing process, also called nonlinear cross-polarization interaction [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. For this last particular case, it has been shown that an arbitrarily polarized incident signal can be attracted toward a specific SOP, which is fixed by the polarization of the counter-propagating pump 2 wave injected at the opposite end of the fiber [55].…”
Section: Introductionmentioning
confidence: 99%
“…In resent years, temporal cloak has been widely studied both theoretically and experimentally [1][2][3][4][5][6][7][8][9][10]. It is an analogy with spatial cloak [11] from the space-time duality associated with diffraction and dispersion [12,13].…”
Section: Introductionmentioning
confidence: 99%